Reselling Software – Copyright Exhaustion, A Conundrum to be Solved or a Swan Song in Progress? - Waxlax, Patrick (fi=Turun yliopisto|en=University of Turku|, 2018)
In this master’s thesis the complication of reselling computer programs is examined in the light of the principle of exhaustion. The issues and problems at hand are considered to be the definition, the properties and distribution of the good, the current treaties, law and regulations. Also current technological possibilities and business setups together with customer knowledge are affecting the possibility to resell computer programs on a secondary market. The problems and issues at hand are based upon a series of different beliefs, misbeliefs and views within the above mentioned areas which makes it difficult for to parties involved to understand, agree upon and finally solve. Based upon the problems investigated some potential solutions are presented before the current and possible future situation of exhaustion of rights for computer programs is outlined. The methods and approach chosen and used in this work is partly a doctrinal research approach and partly an investigation on how technology, business and copyright law have been affecting the secondary market of software. The main areas investigated are the E.U. and the U.S. The conclusion of this master’s thesis is that it seems like the problems related to exhaustion will not be solved in the near future for computer programs. It might not even be of such an importance to solve all of them as software in the future may be provided as a form of service.